Review on Reversed-phase High-performance Liquid Chromatography Method Development and Validation for Estimation of Rivaroxaban: Review on Reversed-phase High-performance Liquid Chromatography Method Development and Validation for Estimation of Rivaroxaban - More, Miss. J. V. (International Journal of Pharmaceutical & Biological Archive, 2019)
This review article is proposed to underline method for the development by reversed-phase highperformance liquid chromatography (RP-HPLC) and validation of rivaroxaban in individual and pharmaceutical dosage form. Rivaroxaban is an anti-clotting drug, acts on Factor Xa, and stops the blood clot development. In this study, different types of RP-HPLC methods which are available at present for the determination of rivaroxaban in tablets (Xarelto 10 mg) are studied. There are different types of the methods described for the estimation of this drug such as RP-HPLC, ultra performance liquid chromatography (UPLC), and ultraviolet. However, nowadays, RP-HPLC plays a key role in quantitative determination of drug. The review is focused on HPLC method development that is previously used for rivaroxaban. Literature study carried on RP-HPLC, high-performance thin-layer chromatography, and UPLC methods of rivaroxaban. The center of study was to develop as well as validate a stable, economic, and rapid. The RP-HPLC method for assessment of rivaroxaban in its bulk formulation. Here, a new aspect for this method was developed which revealed high sensitivity and reproducibility. The developed method by RP-HPLC was validated by guidelines of ICH.